Reproductive performance and fertility traits in Madrasin cattle: The influence of growth differentiation factor-9 gene expression on reproductive tract size, cervical mucus characteristics, and fertility rate - Budi Utomo; Rimayanti Rimayanti; Rochmah Kurnijasanti; Nurhusien Yimer Degu; Athhar Manabi Diansyah; Muhammad Fajar Amrullah (Veterinary World, 2025)
Background and Aim: The growth differentiation factor-9 (GDF-9) gene is recognized as a critical regulator of ovarian function and fertility in cattle. However, its role in crossbred populations, particularly Madrasin cattle (Madura × Simmental cross), remains underexplored. Understanding the genetic underpinnings of fertility traits in this crossbreed could provide valuable insights for improving reproductive efficiency in Indonesia’s livestock sector. This study aimed to investigate the relationship between GDF-9 gene expression and reproductive traits, specifically reproductive tract size (RTS), cervical mucus characteristics, and fertility rate, in Madrasin cows.